Synthesis of copolyurethane-ureas containing nickel and zinc 4,4'-dihydroxysaltrien complexes in the presence of dialcohols or diamines - Prakaywan Tachaprasertporn (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2006